POLA DOMINANSI CAPIT PADA Uca spp. (DECAPODA: OCYPODIDAE) - Dewi Citra Murniati (The East Java Biological Society, 2010)
Uca spp was a unique crab species marked with asymmetry of the cheliped. A major cheliped and a minor cheliped has different function. Major cheliped size is several times of minor cheliped size (cheliped dominance pattern). Each species has different cheliped dominance pattern. This study was done to describe cheliped dominance pattern of three Uca species. Major cheliped length and minor cheliped length of twenty male of U. dussumieri, U. vocans and U. perplexa were examined. Cheliped dominance pattern obtained by compared the major cheliped length to minor cheliped length. The two-tailed single sample t test showed similar cheliped dominance pattern within Uca species (P > 0.001). The Kruskal-Wallis test showed different cheliped dominance pattern among Uca species (P>0.001). The cheliped dominance pattern of U. dussumieri, U. vocans and U. perplexa are 5.09, 4.24 dan 4.75. Size and morphology of manus, cheliped finger and cheliped gap result in total length of cheliped.